Sputtering target

A Cr-based alloy sputtering target with optimized B and Mo/W content and microstructure addresses the issues of fine crystal structure and adhesion in existing targets, reducing cracking and enhancing film quality for applications like perpendicular magnetic recording media.

JP2025065568AActive Publication Date: 2025-04-21SANYO SPECIAL STEEL CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023161574
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-04-21
Estimated Expiration
2043-09-25

AI Technical Summary

Technical Problem

Existing sputtering targets do not provide sufficiently fine crystal structure thin films and adhesion to glass substrates, and the addition of B, W, and Mo to Cr alloys leads to cracking issues during sputtering.

Method used

A Cr-based alloy sputtering target with specific compositions and microstructures, including B and Mo or W, is developed. The target has a matrix of Cr phases with dispersed chromium boride and molybdenum or tungsten boride phases, optimized to prevent cracking and enhance film quality.

Benefits of technology

The target is less likely to crack during sputtering and produces high-quality thin films with fine crystal structures and improved adhesion to glass substrates, suitable for applications like perpendicular magnetic recording media.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025065568000001
    Figure 2025065568000001
  • Figure 2025065568000002
    Figure 2025065568000002
  • Figure 2025065568000003
    Figure 2025065568000003
Patent Text Reader

Abstract

To provide a sputtering target which is not susceptible to breakage during sputtering and enables the achievement of a high-quality thin film by being used for sputtering.SOLUTION: This sputtering target is made of a Cr-based alloy. The Cr-based alloy contains B. The Cr-based alloy also contains Mo or W. The content of B is 5 at% or more and 30 at% or less. The total content of Mo and W is 5 at% or more and 30 at% or less. The content of B is equal to or greater than the total content of Mo and W. The total content of B, Mo, and W is 40 at% or less. The ratio of X-ray diffraction peak P2 with respect to the (110) plane of the Mo phase to X-ray diffraction peak P1 with respect to the (110) plane of the Cr phase is 10% or less. The ratio of X-ray diffraction peak P3 with respect to the (110) plane of the W phase to the peak P1 is 50% or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present specification discloses a target for use in sputtering for forming a thin metal film. [Background technology]

[0002] Sputtering is known as a method for forming thin films. In sputtering, a target is used. In sputtering, positive ions in the plasma collide with the target. These collisions cause atoms to fly out of the target. These atoms then adhere to the substrate, forming a thin film.

[0003] An example of a sputtering target is disclosed in JP 2014-164780 A. The target disclosed in this publication is obtained by sintering powder. The material of this powder is a Cr-based alloy. From this target, a thin film (adhesion layer) that is homogeneous and has fine crystal grains can be obtained. This thin film is suitable for perpendicular magnetic recording media. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP2014-164780A Summary of the Invention [Problem to be solved by the invention]

[0005] Thin films are required to have fine crystal structures and good adhesion to the glass substrate. The target disclosed in JP 2014-164780 A does not provide a thin film with a sufficiently fine crystal structure and good adhesion. Adding B, W, and Mo to the Cr alloy is effective for fine crystal structures and good adhesion to the glass substrate. However, adding these elements causes problems such as particles during sputtering and cracking of the target.

[0006] The applicant's intention is to provide a target which is unlikely to break during sputtering and which, when subjected to sputtering, can provide a high-quality thin film. [Means for solving the problem]

[0007] The material of the sputtering target disclosed in this specification is a Cr-based alloy containing B and also containing Mo or W. In this Cr-based alloy, the content of B is 5 at% or more and 30 at% or less and is equal to or greater than the total content of Mo and W, the total content of Mo and W is 5 at% or more and 30 at% or less, and the total content of B, Mo and W is 40 at% or less. The ratio of the X-ray diffraction peak relating to the (110) plane of the Mo phase to the X-ray diffraction peak relating to the (110) plane of the Cr phase is 10% or less. The ratio of the X-ray diffraction peak relating to the (110) plane of the W phase to the X-ray diffraction peak relating to the (110) plane of the Cr phase is 50% or less.

[0008] Preferably, the sputtering target has a flexural strength of 300 MPa or more in a three-point bending test.

[0009] Preferably, the oxygen content of the Cr-based alloy is 3000 ppm or less.

[0010] The method for producing a sputtering target disclosed in the present specification includes the steps of: (1) providing a first powder, the material of which is CrB; (2) preparing a second powder, the second powder being MoB or WB; (3) providing a third powder, the third powder having a material of Cr; (4) mixing the first powder, the second powder, and the third powder to obtain a mixed powder; and (5) A step of pressing and heating the mixed powder. Includes.

[0011] Preferably, in step (1), a first powder having an average particle diameter D50 of 1 μm or more and 10 μm or less is prepared, in step (2), a second powder having an average particle diameter D50 of 1 μm or more and 10 μm or less is prepared, and in step (3), a third powder having an average particle diameter D50 of 20 μm or more is prepared. Effect of the Invention

[0012] This sputtering target can provide a high quality thin film, and is less likely to crack during sputtering. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] Hereinafter, preferred embodiments will be described in detail with reference to the drawings as appropriate.

[0014] [Cr-based alloy] The material of the sputtering target according to the present embodiment is a Cr-based alloy. This Cr-based alloy contains B. This Cr-based alloy further contains Mo or W. The material of the target may be a Cr-based alloy containing Mo and substantially not containing W. The material of the target may be a Cr-based alloy substantially not containing Mo and containing W. The material of the target may be a Cr-based alloy containing Mo and also containing W. Preferably, in this Cr-based alloy, the balance of Cr, B, Mo and W is an inevitable impurity.

[0015] [Metal structure] A preferred metal structure of the target has a matrix of a Cr phase. A chromium boride phase is dispersed in the matrix. Examples of the chromium boride phase include a CrB phase and a Cr2B phase. A molybdenum boride phase or a tungsten boride phase is further dispersed in the matrix. Examples of the molybdenum boride phase include a MoB phase and a Mo2B phase. Examples of the tungsten boride phase include a WB phase and a W2B phase. The target may have a metal structure in which the molybdenum boride phase is dispersed in the matrix and the tungsten boride phase is not dispersed in the matrix. The target may have a metal structure in which the molybdenum boride phase is not dispersed in the matrix and the tungsten boride phase is dispersed in the matrix. The target may have a metal structure in which the molybdenum boride phase is dispersed in the matrix and the tungsten boride phase is dispersed in the matrix. A Mo phase or a W phase may be dispersed in the matrix.

[0016] [Application] A thin film can be formed by sputtering using this target. Since the Cr-based alloy contains B and also Mo or W, the crystal grains of the thin film are fine. This thin film is suitable for various applications. A typical application of the thin film is as an adhesion layer of a perpendicular magnetic recording medium. This adhesion layer can suppress orientation in the perpendicular magnetic recording medium.

[0017] Chromium Cr can contribute to the non-magnetic, adhesive and corrosion resistance of the adhesive layer. Cr has a BCC structure and has a lattice constant with a small mismatch with the (001) layer (such as an MgO layer) on which the adhesive layer is laminated. Cr can suppress the orientation of the layer on which the adhesive layer is laminated. From these viewpoints, the Cr content in the Cr-based alloy is preferably 60 at% or more. From the viewpoint that the Cr-based alloy can contain sufficient Cr, the total content of B, Mo and W is preferably 40 at% or less.

[0018] As described above, the Cr-based alloy may contain a Cr phase and a CrB phase. The Cr phase has extremely excellent toughness. The toughness of the CrB phase is inferior to that of the Cr phase. However, the CrB phase has a toughness superior to that of other chromium borides. A metal structure containing the Cr phase and the CrB phase can suppress cracking of the target during sputtering.

[0019] [Boron (B)] B combines with Cr, Mo, or W. In the target, B exists as a boride. It is presumed that this boride pins the growth of crystal grains. A thin film with a small crystal grain size can be formed from this target. Furthermore, B can realize a structure without grain boundaries (amorphous). This structure is homogeneous and isotropic. This structure can contribute to the smoothness of the thin film. From these viewpoints, the B content in the Cr-based alloy is preferably 5 at% or more, more preferably 10 at% or more, and particularly preferably 15 at% or more. From the viewpoint of suppressing cracking of the target during sputtering, this content is preferably 30 at% or less. Furthermore, B improves the hardness of the thin film. There is a problem in that the adhesion of the adhesion layer decreases due to small scratches and defects that occur during film formation. Therefore, a hard material that is difficult to be scratched is required for the adhesion layer. From the viewpoint of hardness to ensure adhesion, the B content in the Cr-based alloy is preferably 5 at% or more, more preferably 10 at% or more, and particularly preferably 15 at% or more. From the viewpoint of suppressing cracking of the target during sputtering, this content is preferably 30 at % or less.

[0020] [Molybdenum (Mo), Tungsten (W)] Mo and W have high hardness. Mo and W have high melting points. A thin film having high hardness and excellent thermal stability can be obtained from a sputtering target containing Mo or W. This characteristic improves the adhesion of the film like B. From this viewpoint, the total content of Mo and W in the Cr-based alloy is preferably 5 at% or more, more preferably 10 at% or more, and particularly preferably 15 at% or more. From the viewpoint of suppressing cracking of the target during sputtering, this content is preferably 30 at% or less.

[0021] In the target, most of the Mo can exist as the MoB phase. The amount of Mo present as a single phase is small or zero. The MoB phase can contribute to the toughness of the target. The MoB phase is less likely to be the starting point of cracks during sputtering than the Mo phase. In a target that contains sufficient Mo and in which most of this Mo exists as the MoB phase, it is possible to achieve both suppression of cracks during sputtering and high quality of the thin film.

[0022] Among the multiple peaks of the Cr phase obtained by X-ray diffraction, the peak P1 related to the (110) plane is the largest. Among the multiple peaks of the Mo phase obtained by X-ray diffraction, the peak P2 related to the (110) plane is the largest. The Mo phase is brittle, so it is likely to become the starting point of cracks, and should be as zero and fine as possible. If Mo exists as an MoB compound, it contributes to hardness and toughness. The brittle structure disappears and cracks disappear. When Mo50B is used as the Mo source, the MoB compound exists mainly as Mo2B. MoB4 is brittle, so it is better not to have it. MoB has the same level of toughness as Mo2B, so it does not matter whether it is present or not. The CrB phase is the most stable CrB compound, and it is better that CrB2 and Cr5B3 do not exist. When Cr50B is used as the starting material, all CrB compounds are CrB phase, and CrB2 and Cr5B3 do not exist. The target is less likely to crack when sputtering because the parent phase is pure Cr, which has higher toughness than pure Mo or pure W, and Mo and W exist as borides. From this perspective, the ratio (P2 / P1) of the X-ray diffraction peak P2 relating to the (110) plane of the Mo phase to the X-ray diffraction peak P1 relating to the (110) plane of the Cr phase is preferably 10% or less, more preferably 7% or less, and particularly preferably 5% or less. Ideally, this ratio is 0%.

[0023] W is easy to precipitate, and pure W is scattered even if W50B is used as the W source and pure W is not used as the starting material. However, this W is a small amount and is scattered small, so it is unlikely to cause cracks. Therefore, if the ratio (P3 / P1) of the X-ray diffraction peak P3 on the (110) plane of the W phase to the X-ray diffraction peak P1 on the (110) plane of the Cr phase is 50% or less, a peak of pure W may be observed. In the target, most W can exist as the WB phase. W can also exist as a single phase, although in small amounts. The WB phase can contribute to the toughness of the target. The WB phase is less likely to be the starting point of cracks during sputtering than the W phase. In a target that contains sufficient W and in which much of this W exists as the WB phase, it is possible to suppress cracks during sputtering and achieve high quality of the thin film at the same time. The WB compound mainly exists in the phase, W2B. When W50B is used as the W source, the WB compound is mainly present as W2B. WB2 is brittle, so it is better not to have it. WB has the same level of toughness as W2B, so it doesn't matter whether it's there or not.

[0024] Among the multiple peaks of the W phase obtained by X-ray diffraction, the peak P3 relating to the (110) plane is the largest. From the viewpoint of preventing cracking of the target during sputtering, the ratio (P3 / P1) of the X-ray diffraction peak P3 relating to the (110) plane of the W phase to the X-ray diffraction peak P1 relating to the (110) plane of the Cr phase is preferably 50% or less, more preferably 30% or less, and particularly preferably 10% or less. Ideally, this ratio is 0%.

[0025] From the viewpoint of achieving small ratios (P2 / P1) and (P3 / P1), it is preferable that the content (at%) of B is equal to or larger than the total content (at%) of Mo and W. The ratio (Pa / Pb) of the content Pa (at%) of B to the total content Pb (at%) of Mo and W is preferably 1 / 1 or more and 6 / 1 or less. This ratio (Pa / Pb) is more preferably 4 / 1 or less, and particularly preferably 3 / 1 or less.

[0026] Peaks P1, P2 and P3 are measured by an X-ray diffraction device. A test piece for X-ray diffraction is cut out from a target by a wire-cut method. The surface of the test piece is smoothed by polishing. The measurement conditions are as follows: Test piece size: 10mm x 20mm x 5mm X-ray source: CuKα ray Scan speed: 4° / min 2θ:20-80° Peaks (peak intensities) are read from the chart obtained by this X-ray diffraction.

[0027] [impurities] The Cr-based alloy may contain oxygen as an impurity. The oxygen content (mass basis) is preferably 3000 ppm or less. A target made of this Cr-based alloy is less likely to crack during sputtering. Furthermore, a thin film with fewer particles can be obtained from this target. From these viewpoints, the oxygen content is more preferably 2000 ppm or less, and particularly preferably 1000 ppm or less. Ideally, the oxygen content is less than the detection limit.

[0028] [Transverse bending strength] The flexural strength of the target is preferably 300 MPa or more. This target is less likely to crack during sputtering. From this viewpoint, the flexural strength is more preferably 400 MPa or more, and particularly preferably 500 MPa or more.

[0029] The flexural strength is measured by a three-point bending test in accordance with the provisions of "JIS Z 2511." Test pieces for the three-point bending test are cut from the target by the wire cutting method. The measurement conditions are as follows: Test piece size: 2mm x 2mm x 20mm Distance between fulcrums: 10mm The flexural strength BS (MPa) is calculated by the following formula. BS = 3 / 2 × P × L / (t 2 × W) P: Load at break (kN) L: Distance between fulcrums (mm) t: thickness of test piece (mm) W: width of sample (mm)

[0030] [Manufacturing method] The sputtering target can be obtained by powder metallurgy. A preferred method for producing the sputtering target is: (1) providing a first powder, the material of which is CrB; (2) preparing a second powder, the second powder being MoB or WB; (3) providing a third powder, the third powder having a material of Cr; (4) mixing the first powder, the second powder, and the third powder to obtain a mixed powder; and (5) Pressurizing and heating the mixed powder By applying pressure and heat, a sputtering target, which is a sintered body, is obtained. This target is processed to a predetermined size and is used for sputtering.

[0031] Since the material of the first powder is CrB, this first powder contains 50 at% Cr and 50 at% B. Since the material of the second powder is MoB or WB, this second powder contains 50 at% Mo or W and 50 at% B. The B contained in the Cr-based alloy of the target originates from the first powder and the second powder. This Cr-based alloy does not contain any component derived from the powder whose material is simple B. In this target, B can be uniformly dispersed. A homogeneous thin film can be formed from this target. A thin film with few particles can be obtained from this target.

[0032] The Mo contained in the target Cr-based alloy originates from the second powder. This Cr-based alloy does not contain any components originating from the powder made of simple Mo. This target can achieve a small ratio (P2 / P1). This target is less likely to crack during sputtering. In this target, Mo can be uniformly dispersed. A homogeneous thin film can be formed from this target. Since the Cr-based alloy does not contain any components originating from the powder made of simple Mo, the peak P2 is almost zero.

[0033] The W contained in the Cr-based alloy target is derived from the second powder. This Cr-based alloy does not contain any components derived from the powder made of simple W. A small ratio (P3 / P1) can be achieved in this target. This target is less likely to crack during sputtering. W can be uniformly dispersed in this target. A homogeneous thin film can be formed from this target. Although the Cr-based alloy does not contain any components derived from the powder made of simple W, a small amount of W can be generated from WB during heating. Therefore, a small-sized peak P3 can be observed in this target.

[0034] In this manufacturing method, MoB is prepared as a Mo source, and WB is prepared as a W source. MoB and WB are also B sources. However, MoB and WB alone are insufficient as B sources. In this manufacturing method, CrB is also prepared as a B source. With a sufficient B source, a target in which the B content is the same as or greater than the total content of Mo and W can be obtained. In this target, small ratios (P2 / P1) and (P3 / P1) can be achieved.

[0035] [Average particle diameter D50] The average particle diameter D50 of the first powder is preferably 10 μm or less. This first powder can contribute to uniform dispersion of B. From this viewpoint, the average particle diameter D50 is more preferably 8 μm or less, and particularly preferably 7 μm or less. From the viewpoint of handling, the average particle diameter D50 is preferably 1 μm or more.

[0036] The average particle diameter D50 of the second powder is preferably 10 μm or less. This second powder can contribute to uniform dispersion of Mo and W. From this viewpoint, the average particle diameter D50 is more preferably 8 μm or less, and particularly preferably 7 μm or less. From the viewpoint of handling, the average particle diameter D50 is preferably 1 μm or more.

[0037] The average particle diameter D50 of the third powder is preferably 20 μm or more. The particles of this third powder are generally larger than the particles of the first powder and the second powder. Since this third powder is mixed with the first powder and the second powder, a target with a low oxygen content can be obtained even though the average particle diameter D50 of the first powder and the second powder is small. Specifically, a target with an oxygen content of 3000 ppm or less can be obtained by this manufacturing method. This target is less likely to break during sputtering. Since B, Mo, and W are not derived from the third powder, even if the average particle diameter D50 of the third powder is large, uniform dispersion of B, Mo, and W can be achieved. From the viewpoint of the target's resistance to cracking, the average particle diameter D50 of the third powder is more preferably 40 μm or more, and particularly preferably 50 μm or more. This average particle diameter D50 is preferably 250 μm or less.

[0038] The average particle diameter D50 of each powder is measured by a laser diffraction / scattering particle size distribution analyzer. The particle diameter when the cumulative volume is 50% in the cumulative volume curve of the powder is obtained.

[0039] From this target, an adhesion layer for a perpendicular magnetic recording medium can be obtained by sputtering. From this target, other thin films can be obtained by sputtering.

[0040] The present specification is also directed to a method for producing a thin film, the method comprising the steps of: (1) preparing a target, the material of which is a Cr-based alloy containing B and Mo or W, the B content in the Cr-based alloy being 5 at% or more and 30 at% or less and equal to or greater than the total content of Mo and W, the total content of Mo and W being 5 at% or more and 30 at% or less, the total content of B, Mo and W being 40 at% or less, a ratio of an X-ray diffraction peak corresponding to a (110) plane of the Mo phase to an X-ray diffraction peak corresponding to a (110) plane of the Cr phase being 10% or less, and a ratio of an X-ray diffraction peak corresponding to a (110) plane of the W phase to an X-ray diffraction peak corresponding to a (110) plane of the Cr phase being 50% or less; and (2) subjecting the target to sputtering This manufacturing method can produce high quality thin films, such as adhesion layers for perpendicular magnetic recording media. EXAMPLES

[0041] The effects of the sputtering targets according to the examples will be explained below, but the scope of the present specification should not be construed as being limited based on the description of these examples.

[0042] [Example 1] A third powder was prepared. The material of this third powder was Cr. The average particle diameter D50 of this third powder was 60 μm. Furthermore, a second powder was prepared. The material of this second powder was MoB. This MoB contained 50 at% Mo and 50 at% B. The average particle diameter D50 of this second powder was 5 μm. The third powder and the second powder were put into a V-type mixer to obtain a mixed powder. The mixed powder was filled into a can made of carbon steel, having a diameter of 200 mm and a length of 10 mm. After the powder was degassed in vacuum, a billet was made by HIP. The HIP conditions were as follows. Sintering temperature: 1000℃ Pressure: 120MPa Retention time: 5 hours This billet was sliced ​​to obtain the sputtering target of Example 1.

[0043] [Examples 2-21 and Comparative Examples 1-18] Sputtering targets of Examples 2-21 and Comparative Examples 1-18 were obtained in the same manner as in Example 1, except that the starting materials and sintering temperatures were as shown in Tables 1 and 2 below.

[0044] [Oxygen content] A test piece was cut from the target by wire cutting. The mass of this test piece was about 1 g. The surface of this test piece was polished, and the oxygen content was measured using an oxygen / nitrogen analyzer (manufactured by Horiba, Ltd., product name "EMGA-920"). The results are shown in Tables 1 and 2 below.

[0045] [X-ray diffraction] The target was subjected to X-ray diffraction by the method described above. The ratio (P2 / P1) of the X-ray diffraction peak P2 related to the (110) plane of the Mo phase to the X-ray diffraction peak P1 related to the (110) plane of the Cr phase was calculated. Furthermore, the ratio (P3 / P1) of the X-ray diffraction peak P3 related to the (110) plane of the W phase to the peak P1 was calculated. The results are shown in Tables 3 and 4 below. When the peak P2 could not be distinguished from noise and the ratio (P2 / P1) was 5% or less, it was indicated as "<5%". When the peak P3 could not be distinguished from noise and the ratio (P3 / P1) was 5% or less, it was indicated as "<5%".

[0046] [Deflection test] The flexural strength of the target was measured by the method described above, and the results are shown in Tables 3 and 4 below.

[0047] [Number of particles in thin film] A thin film was formed by sputtering a target (diameter: 95 mm, thickness: 2 mm) under the following sputtering conditions: Substrate material: cleaned glass Chamber atmosphere: atmospheric pressure 1×10 -4 The pressure was evacuated to below 0.6 Pa, and 99.99% pure Ar gas was introduced at 0.6 Pa. Thin film thickness: 20nm The thin film was observed with an Optical Surface Analyzer to count the number of particles having a size of 0.1 μm or more. The results are shown in Tables 3 and 4 below.

[0048] [Crystal grain size] The thin film was observed by TEM to measure the average crystal grain size. The ratio of this average crystal grain size to the crystal grain size of Cr in Comparative Example 1 was calculated. The results are shown in Tables 3 and 4 below.

[0049] [Hardness of sputtered film] A test piece was taken from the single layer film obtained by the above-mentioned sputtering, and the hardness of the thin film was measured by a nanoindentation method. The ratio to the hardness of Cr in Comparative Example 1 was calculated. The results are shown in Tables 3 and 4 below.

[0050] [Table 1]

[0051] [Table 2]

[0052] [Table 3]

[0053] [Table 4]

[0054] As is clear from Tables 3 and 4, the sputtering targets of each Example have excellent bending strength. Furthermore, the thin films obtained from these targets have few particles, small crystal grain size, and excellent hardness. From these evaluation results, the superiority of this sputtering target is clear. [Industrial Applicability]

[0055] Thin films for various applications can be produced from the sputtering targets described above.

Claims

1. The material is a Cr-based alloy containing B and also containing Mo or W, In the above Cr-based alloy, the content of B is 5 at% or more and 30 at% or less and is equal to or greater than the total content of Mo and W, the total content of Mo and W is 5 at% or more and 30 at% or less, and the total content of B, Mo and W is 40 at% or less, a ratio of an X-ray diffraction peak relating to the (110) plane of the Mo phase to an X-ray diffraction peak relating to the (110) plane of the Cr phase is 10% or less; A sputtering target, in which a ratio of an X-ray diffraction peak relating to a (110) plane of a W phase to an X-ray diffraction peak relating to a (110) plane of a Cr phase is 50% or less.

2. 2. The sputtering target according to claim 1, wherein the Cr-based alloy has an oxygen content of 3000 ppm or less.

Citation Information

Patent Citations

  • Cr target material and its production

    JP2000199055A

  • Cr ALLOY TARGET MATERIAL AND ITS PRODUCTION METHOD

    JP2005336611A

  • Sputtering target and method for fabricating the same

    JP2008169464A

  • Coated tool for machining titanium alloys and high-temperature alloys and its manufacturing method

    JP2022552402A

  • Cr ALLOY FOR MAGNETIC RECORDING AND SPUTTERING TARGET MATERIAL, AND PERPENDICULAR MAGNETIC RECORDING MEDIUM USING THE SAME

    JP2014164780A